2007
DOI: 10.1002/chin.200732167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel Substituted Purine Derivatives as Potential Anticancer, anti‐HIV‐1 and Antimicrobial Agents.

Abstract: Some of the products show antitumor activity [e.g. (VIIa), (VIIb), (IIIa)]. Compound (IXb) possesses moderate in vitro anti-HIV activity and various derivatives exhibit promising antimicrobial effects. -(RIDA, S. M.; ASHOUR, F. A.; EL-HAWASH*, S. A. M.; EL-SEMARY, M. M.; BADR, M. H.; Arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…In conclusion, we have synthesized 9-substituted derivatives of tert-butyl 6-(9H-purin-6-ylthio) hexylcarbamate in good yields and characterized by 1 H NMR, IR and LCMS spectral data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, we have synthesized 9-substituted derivatives of tert-butyl 6-(9H-purin-6-ylthio) hexylcarbamate in good yields and characterized by 1 H NMR, IR and LCMS spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…The purine ring system possesses undisputed biological importance and it is considered to be one of the most important heterocyclic rings in nature [1]. Cells obtain purine nucleotides through two separate metabolic pathways, de novo purine synthesis and salvage of extracellular purine bases and nucleotides [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a continuation to previous efforts (Rida et al, 2005(Rida et al, , 2007 aiming to locate novel synthetic lead compounds for future development as anticancer, antiviral and/or antimicrobial agents. In our earlier study (Rida et al, 2007), we reported the synthesis and evaluation of in vitro anticancer, anti-HIV-1 and antimicrobial activities of a number of new 8-substituted methylxanthines.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier study (Rida et al, 2007), we reported the synthesis and evaluation of in vitro anticancer, anti-HIV-1 and antimicrobial activities of a number of new 8-substituted methylxanthines. The compounds were designed to comprise the purine nucleus linked at C-8 with various heterocyclic ring systems either directly or through a two-nitrogen atom spacer.…”
Section: Introductionmentioning
confidence: 99%